The Influence Of Lifestyle And Financial Literacy On The Use Of Digital Payment Among Students At Dehasen University Bengkulu - Yoga Anugra Pratama; Sulisti Afriani; M Rahman Febliansa (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the influence of lifestyle and financial literacy on the use of digital payment among students at Dehasen University Bengkulu. The background of this research is the rapid development of financial technology that encourages students to adopt cashless transactions. However, the lack of financial literacy has led many students to behave consumptively. This research employs a quantitative associative method with 110 student respondents selected using purposive sampling. Data were collected through questionnaires using a Likert scale and analyzed using multiple linear regression with the help of SPSS software, including validity tests, reliability tests, classical assumption tests, t-test, F-test, and the coefficient of determination (R²). The results of the study show that lifestyle and financial literacy have a significant influence on the use of digital payment, both partially and simultaneously. The coefficient of determination (R²) value of 0.670 indicates that 67% of the variation in digital payment use can be explained by lifestyle and financial literacy, while the remaining 33% is influenced by other factors. These findings suggest that students with a higher level of financial literacy and a more productive lifestyle tend to use digital payment more wisely and efficiently. Therefore, improving financial literacy is essential to encourage responsible digital financial behavior among university students.